ABIOTIC STRESS RESPONSE-ASSOCIATED PROTEINS IN A SALT TOLERANT STRAIN OF THE CYANOBACTERIUM FREMYELLA DIPLOSIPHON: A POTENTIAL BIOFUEL AGENT - Behnam TABATABAI; Viji SITTHER (Journal of Construction Project Management and Innovation)
Cyanobacteria have gained great significance as a clean green alternative to fossil fuels as they are renewable and sustainable. Fremyella diplosiphon is a potential biofuel-producing cyanobacterium that efficiently captures light energy for photosynthesis. Efforts in our laboratory have been aimed to identify salt response pathways in this organism to develop strategies to enhance halotolerance in this model organism. In this study, protein expression in wild type and halotolerant mutant F. diplosiphon strains was compared using two-dimensional polyacrylamide gel electrophoresis and matrix-assisted laser desorption/ionization time of flight mass spectrometry. Of the 16 up-regulated proteins identified in the mutant, tripartite ATP-independent periplasmic (TRAP) transporter solute receptor was found to assist in salt-stress response with a significant hit to a corresponding spot with a score of 669 and 21% sequence coverage. Another protein, elongation factor Tu, linked to enhanced abiotic stress tolerance was significantly matched to a spot with a score of 1358 and 52% sequence coverage. Results of our study indicate that TRAP transporter solute receptor likely assists in enhancing halotolerance of the mutant, while elongation factor Tu is up-regulated in response to heat shock. These findings enable better understanding of F. diplosiphon salt-stress response paving the way for novel approaches in enhancing its halotolerance, leading to viable options leading to biofuel production.